Penerapan Sistem Informasi Hipertensi Berbasis Android di Apotek Jatinom Farma Klaten - Yunita Wisda Tumarta Arif (LPPM Universitas Duta Bangsa Surakarta, 2023)
Hypertension or high blood pressure is a disorder of the blood vessels which results in the supply of oxygen and nutrients carried by the blood being obstructed to reach the body tissues that need them, a condition where blood pressure equals or exceeds 140mmHg systolic and or equals or exceeds 90mmHg diastolic in a person who not currently taking antihypertensive medication. The pharmacist's role is required to increase knowledge, skills, and behavior in order to be able to carry out direct interactions with patients. The forms of this interaction include the provision of drug information and counseling to patients who need it. From the results of observations and interviews, many people come to the pharmacy to buy drugs and counseling related to hypertension. The solution to this problem is an information system that can be accessed by pharmacists and pharmacy staff, so that information related to hypertension can be conveyed to people who need it by implementing an Android-based Hypertension Information System at the Jatinom Farma Pharmacy, Klaten. Android was chosen as the basis for the Hypertension Information System because of the ease of implementation on devices, an Android-based Hypertension Information System can be installed on any pharmacy staff's gadget. The result of this service is that the system can be put to good use by Jatinom Farma pharmacy staff, and helps in service.